Using Raw Earth Construction Systems on Contemporary Buildings: Reflections on Sustainability and Thermal Efficiency - Marques Bruno (EDP Sciences, 2021)
Although the existence of building energy efficiency policies for several years, studies show that up to 74% of the participant consider their house uncomfortable. European policies favored construction solutions focused on insulating materials rather than other solutions which traditionally were used and proved to be effective. Construction system that uses earth as construction material showed for centuries that it can offer high levels of thermal comfort in a passive way, with a highly sustainable and quasi-neutral environmental impact. With this paper, a study on the thermal performance of three contemporany rammed earth buildings is presented. The aim is to analyze thermal comfort over a critical period of time. It is expected that earth construction proves to be a good choice, creating a sustainable and better integration with the local environment, with almost zero energy incorporation, promoting the local work craftmen and with a construction range price below the common construction systems.